(untitled) (Iraqi Journal of Civil Engineering, 2012)
This study was determined specified characteristics of Iraqi silica sand , touse it in the drinking water treatment rapid gravity filters. These properties includes grain size ,uniformity coefficient , grain shape , porosity , density , durability, chemical content and capability of solubility in the acid ..this study explained that the Iraqi silica sand has high degree at mechanical and chemical stabilities .The e filter column was operate for many cycles , the average results of raw water and treatedwater for variable values (turbidity , total suspended solids and total bacterial count) was taken . The study showed that possibility of use the Iraqi silica sand in the westernIraqi desert in the rapid gravity drinking water treatment plant filters . when the raw water has initial turbidity (5.24 NTU) ,the study and the experimental tests showedthat the average removal efficiency of turbidity , T.S.S ,and T.B.C of (82.9%,82.8%and 79.5%) respectively . when the raw water has initial turbidity (9.58 NTU) ,the study and the experimental tests showed that the average removal efficiency of turbidity , T.S.S ,and T.B.C of (79.4%,78.7% and 74.1%) respectively . when the rawwater has initial turbidity (28.35 NTU) ,the study and the experimental tests showedthat the average removal efficiency of turbidity , T.S.S ,and T.B.C of (72.6%,72.7%and 60.9%) respectively